The Role Of Gamification in Online Learning Platforms: A Case Study On Student Motivation and Achievement - Adebayo Chukwu; Nneka Eze; Emeka Okoye (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This article explores the effects of gamification on student motivation and achievement in online learning platforms. By examining gamified elements such as leaderboards, badges, and progress tracking, the study analyzes how these features impact students’ engagement and performance in virtual classrooms. Results indicate that gamification can significantly enhance motivation and encourage active participation, although the effectiveness may vary based on age and learning style. This research provides valuable insights into how gamified features can optimize online learning environments and improve academic outcomes, supporting the integration of gamification strategies in educational technology.